EFFECTS OF AERATION ON GROUNDWATER QUALITY FOR IRRIGATION - Zoran Rajić; Vaso Novaković; Miladin Gligorić; Časlav Lačnjevac; Ranko Grujić; Dragić Živković (Ekonomika Poljoprivrede (1979), 2012)
Volatility in agricultural production caused by the reliance on natural factors, and water is one of the basic, which provides greater production. Volatility in agricultural production caused by the reliance on natural factors, and water is one of the basic, which provides greater production. The authors in their professional praxis have seen that the presence and absence of vadose zone in the upper part of aquifer, with inter-granulary porosity type, is a prerequisite for enhanced concentrations of iron and manganese in groundwater. The natural aeration zone in vadose zone of the upper part of aquifer enables additional enrichment of groundwater with oxygen, which is spent on the account of biochemical processes in the direction of their flow. The absence of this zone in aquifer directly influences higher iron and manganese content in groundwater, often above the permissible concentration in drinking water. In order to eliminate this problem, in this paper proposal of future works were made, different of the usual procedure of hydro geological research. It will be possible to examine the effect of aeration of groundwater in the aquifer, during the preparation of wells from which to irrigate the land.